DESAIN UI/UX SISTEM INFORMASI MANAJEMEN MASYARAKAT TINGKAT RT BERBASIS WEB UNTUK MEMINIMALISIR MASALAH SOSIAL - Endar Setyoroso; Ismail (J-ENSITEC, 2023)
The social welfare problems that exist to date have not been fully resolved, marked by the fact that there are still people with social problems. Seeing these problems, creative model formulations are needed in an effort to solve social problems which previously were only done using manual methods characterized by population data collection in a systematic manner. manual, manual delivery of information, weak monitoring of implementation so that it is full of inconsistencies between the order of ideas and implementation, and is unable to raise collective awareness in the community that they are the main actors of change. This research aims to design a management information system for managing RT level data starting from the smallest service level. So this research can support the government in dealing with social problems from the smallest level. The method used in building the system is the design thinking method, starting from empathize, define, ideate, prototype and test. The output of the web-based application is in the form of a map feature, valid and up-to-date data, discussion and complaint forums, a cover letter submission feature, information on community activities, then this information will be received by the RT head and the RT neighborhood community and even the central government can get information on community welfare development at this web-based system.